2009
DOI: 10.1093/bja/aep253
|View full text |Cite
|
Sign up to set email alerts
|

Impact of opioid rescue medication for breakthrough pain on the efficacy and tolerability of long-acting opioids in patients with chronic non-malignant pain

Abstract: BackgroundThere is little evidence that short-acting opioids as rescue medication for breakthrough pain is an optimal long-term treatment strategy in chronic non-malignant pain. We compared clinical studies of long-acting opioids that allowed short-acting opioid rescue medication with those that did not, to determine the impact of opioid rescue medication use on the analgesic efficacy and tolerability of chronic opioid therapy in patients with chronic non-malignant pain.MethodsWe searched MEDLINE (1950 to July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 64 publications
0
16
0
4
Order By: Relevance
“…Subsequently, our aim consisted of performing a multimodal analgesic paradigm, in which the three drugs were combined. It is noteworthy that we recently demonstrated that FEN and PRC interact in a synergic manner on the inhibition of acetic acid-induced nociception in mice (6), and similarly FEN and TRM have been shown to induce synergic antinociceptive effects in the writhing test (14), validating the clinical strategy of using opioidopioid combinations in the management of pain, usually in patients in which opioid tolerance appears (2). On the basis of these results, we expected supra-additive antinociceptive effects when combining the three drugs, and effectively FEN:TRM:PRC displayed a potent synergistic interaction on the inhibition of acetic acid-mediated nociception.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Subsequently, our aim consisted of performing a multimodal analgesic paradigm, in which the three drugs were combined. It is noteworthy that we recently demonstrated that FEN and PRC interact in a synergic manner on the inhibition of acetic acid-induced nociception in mice (6), and similarly FEN and TRM have been shown to induce synergic antinociceptive effects in the writhing test (14), validating the clinical strategy of using opioidopioid combinations in the management of pain, usually in patients in which opioid tolerance appears (2). On the basis of these results, we expected supra-additive antinociceptive effects when combining the three drugs, and effectively FEN:TRM:PRC displayed a potent synergistic interaction on the inhibition of acetic acid-mediated nociception.…”
mentioning
confidence: 62%
“…However, although there is precise categorization of analgesics within drug-drug combinations, these multimodal analgesic approaches are most of the times based on empirical instead of accurate experimental data. In such a way, tramadol (TRM) and paracetamol (PRC) have been revealed as analgesic drugs that would synergically interact with opioid drugs (1,2). Furthermore, the combination of TRM and PRC is also a common multimodal analgesic strategy that has been shown to be effective and generally well tolerated in patients with moderate to severe pain (3).…”
mentioning
confidence: 99%
“…Whereas inflammatory pain is one of the classic symptoms of the inflammatory process, neuropathic pain arises from any of multiple nerve lesions or diseases, with symptoms including hyperalgesia or allodynia (1,2). Some of the most powerful painkillers, including opioids and nonsteroidal anti-inflammatory drugs, are only partially effective and prolonged exposure can cause unwanted effects (3,4). As a result, there is continuous effort to identify novel therapeutics for pain control with alternative biological mechanisms and that elicit fewer side effects.…”
mentioning
confidence: 99%
“…A systematic review of nonrandomized studies by Devulder et al 61 examined the effect of rescue medications on overall analgesic efficacy and adverse events. They examined 48 studies of patients treated with long-acting opioids for chronic noncancer pain and compared the analgesic efficacy and adverse events among those that allowed short-acting opioid rescue medications for breakthrough pain with those that did not allow such rescue medications.…”
Section: In the Adult Ed Patient With An Acute Exacerbation Of Noncanmentioning
confidence: 99%